THE USE OF PROJECT-BASED LEARNING IN IMPROVING THE STUDENTS` SPEAKING SKILL (A Classroom Action Research at One of Primary Schools in Bandung) - Darini Bilqis Maulany (Journal of English and Education, 2013)
The paper reporst on a two-cycle action research conducted at a Year 4 class at one primary school in Bandung. This study aimed to find out whether Project-based Learning could improve young learners’ speaking skill or not and what speaking aspects were improved through PBL. It also aimed to investigate what speaking activities were used in PBL to improve their speaking skill. To collect the data, participatory observation was done for eight meetings and speaking assessment was conducted three times in the first, fifth, and eighth meetings (Pre-test, Post-test 1, Post-test 2). Qualitative analysis was also used in this design of study. The findings show that PBL could improve the students’ speaking skill. It was indicated by the improvement of the students’ speaking aspects adapted from Harries (1984) and Brown (2004) covering comprehension, vocabulary, grammar, fluency, and pronunciation. Of all the five aspects, comprehension and vocabulary were improved most significantly. As for the speaking activities used in PBL, this study used the ones proposed by Brown (2004) and Kayi (2006). Of 21 speaking activities, nine of them were used, namely drilling, storytelling, directed response, picture-cued, translation of limited stretches of discourse, question and answer, discussion, games, and role-play. Based on this study, it is suggested that Project-based Learning is implemented in teaching speaking in primary schools. Keywords:Speaking skill, speaking aspects, speaking activity, young learners, Project-based Learning